Liberalisation policy and social concerns - Sharma, R.D. (1996)
The author examines in details the financial picture of India's national economy emerging after implementation of New Economic Policy, and analyses their impact highlighting the failures. He suggest taking up more structural reforms for obtaining the desired results. - Reproduced
Keywords: Liberalization - India; Economic liberalization